Análisis de la composición gráfica de las ediciones impresa de diario La Hora-Loja y digital de Hora32, periodo enero a abril 2023 - Collaguazo Jaen, Alisson Lilibeth (2024)
The evolution of the media has been the cause of a constant change in the way we access information and consume news. Likewise, the way in which it is presented has evolved, the visual part plays an important role when choosing the media from which we will consume the information. This research was conducted in the city and province of Loja with the purpose of analyzing the elements of graphic composition present in the printed version of the newspaper La Hora-Loja and in the digital newspaper Hora32. The intention is to identify the elements and contrast them. To carry out this work, a qualitative approach was used to obtain the results of the research. Techniques such as literature review, interviews and observation were also used. The tools used were an observation sheet, interviews with design and communication experts, and a focus group. Through the analysis and interpretation of the data it was possible to observe that in the newspaper La Hora there is a careful management of the elements of graphic composition. Elements such as its format, the colors used, its headline, the typographies used, position its brand in the minds of those who consume the information. In the case of Hora32, being a digital media, other graphic elements such as interactivity, multimedia and hypertextuality are incorporated. The conclusions provide us with different data, among them, the printed version of the newspaper La Hora Loja uses graphic elements, but has a style of yesteryear. Hora32, created in a digital environment, adapts to the current model, but lacks a unique identity. The contrast between the print and digital versions emphasizes the importance of considering the platforms used during design. Keywords: digital newspaper; printed newspaper; editorial design; graphic composition.